Deep brain stimulation in Early Onset Parkinson's disease - Krause, Patricia; Reimer, Johanna; Kaplan, Jonathan; Borngräber, Friederike; Schneider, Gerd-Helge; Faust, Katharina; Kühn, Andrea A. (Frontiers in Neurology, 2022)
Introduction: Subthalamic Deep Brain Stimulation (SSTN-DBS) is a safe and well-established therapy for the management of motor symptoms refractory to best medical treatment in patients with Parkinson´s disease (PD). Early intervention is discussed especially for Early-onset PD (EOPD) patients that present with an age of onset ≤ 45-50 years and see themselves often confronted with high psychosocial demands. Methods: We retrospectively assessed the effect of STN-DBS at 12 months follow-up (12-MFU) in 46 EOPD-patients. Effects of stimulation were evaluated by comparison of disease-specific scores for motor and non-motor symptoms including impulsiveness, apathy, mood, quality of life (QoL), cognition before surgery and in the stimulation ON-state without medication. Further, change in levodopa equivalent dosage (LEDD) after surgery, DBS parameter, lead localisation, adverse and serious adverse events as well as and possible additional clinical features were assessed. Results: PD-associated gene mutations were found in 15% of our EOPD-cohort. At 12-MFU, mean motor scores had improved by 52.4±17.6% in the STIM-ON/MED-OFF state compared to the MED-OFF state at baseline (p=0.00; n=42). These improvements were accompanied by a significant 59% LEDD reduction (p<0.001), a significant 14.2±5.7 points reduction of impulsivity (p=0.02; n=35) and a significant 30±50% improvement of QoL (p=0.01). At 12-MFU, 9 patients still worked full- and 6 part-time. Additionally documented motor and/or neuropsychiatric features decreased from n=41 at baseline to n=14 at 12-MFU. Conclusion: The present study-results demonstrate that EOPD patients with and without known genetic background benefit from STN-DBS with significant improvement in motor as well as non-motor symptoms. In line with this, patients experienced a meaningful reduction of additional neuropsychiatric features. Physicians as well as patients have an utmost interest in possible predictors for the putative DBS outcome in a cohort with such a highly complex clinical profile. Longitudinal monitoring of DBS-EOPD-patients over long-term intervals with standardized comprehensive clinical assessment, accurate phenotypic characterization and documentation of clinical outcomes might help to gain insights into disease etiology, to contextualize genomic information and to identify predictors of optimal DBS candidates as well as those in danger of deterioration and/or non-response in the future.